Glucomannan's protective effect on the virulence of Vibrio splendidus in pacific oyster. (September 2016) - Fdhila, Kais; Haddaji, Najla; Chakroun, Ibtissem; Macherki, Mohammed Ezz Eddine; Nefzi, Faten; Bakhrouf, Amina
Abstract: We examine the effect of Glucomannan, extracted from Candida utilis yeast, on immune parameters and resistance to Vibrio splendidus of Crassostreagigas . Our results showed that Glucomannan was a successful anti-adhesive molecule; it exhibited a stronger inhibitory effect on adhesion of Vibrio splendidus in infected Crassostreagigas . Vibrio splendidus viable cells number declined after incubation with Glucomannan. Furthermore, the Glucomannan diet showed higher activity to trigger the immune response against bacteria. Glucomannan applications, in biological control of seafood associated pathogens can be an alternative solution, providing consumer with a product of good quality owing to the use of 40 non-toxic compounds. Based on our results, Glucomannan could be used as a bio-protective culture in oyster's depuration to prevent Vibrio splendidus growth. Highlights: Glucomannan of Candida utilis with commonly used as safe probiotic. Vibrio splendidus is widespread in aquaculture. Glucomannan of C. utilis had an effect on immunity and resistance to V. splendidus of Crassostrea gigas . Glucomannan was a successful anti-adhesive molecule.